Foreign Body Bottom of Pen in Bronchus with and without Atelectasis - Rahmadona Rahmadona; Ade Asyari; Novialdi Novialdi; Fachzi Fitri (Fakultas Kedokteran, Universitas Andalas, 2018)
Introduction: Foreign body aspiration (FBA) is a common case in children. Delayed diagnosis more than 24 hours often increased the risk of complications and mortality. Atelectasis is one of the common complication of FBA. Rigid bronchoscopy under general anaesthesia is the choice of procedure for diagnosis and treatment. Case Report: It was reported two cases foreign body aspirationof a bottom of pen. First case was agirl, aged 6 year-old with foreign body a bottom of pen without lumen in bronchus with atelectasis and second case was a foreign body bottom of penwith lumen in bronchus in a boy, aged12 year-old without atelectasis but late diagnosis. Both cases have been successfully extracted using rigid bronchoscopy. Conclusion: Foreign body without lumen have more acute and severe complication rather than foreign body with lumen. The presence of a lumen within the foreign body allows good ventilation and shows less symptomps. Appropriate diagnosis and treatment will minimize the risk of complications.